Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.2341/09-037l
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Proximal Contact Tightness of Class II Resin Composite Restorations

Abstract: The use of separation rings with sectional matrices provides superior contacts when placing Class II RCRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 17 publications
1
48
0
5
Order By: Relevance
“…The validity of this model was demonstrated by Loomans and others 6 and Saber and others, 19 where it was concluded that the in vitro model is representative of the clinical situation. Natural tooth movement cannot be reproduced in a laboratory setting.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The validity of this model was demonstrated by Loomans and others 6 and Saber and others, 19 where it was concluded that the in vitro model is representative of the clinical situation. Natural tooth movement cannot be reproduced in a laboratory setting.…”
Section: Discussionmentioning
confidence: 96%
“…This can be best achieved by using separation rings. [5][6][7]19 Nevertheless, this study showed that type of composite, possibly volumetric shrinkage, and intensity of polymerization light influence proximal contact tightness. However, a direct cause-and-effect relationship between shrinkage and contact tightness was not established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the proximal contact tightness of the two study groups; Chi-square test is applied; the level of significance was set at 5%; *Statistically significant difference; df: Degree of freedom Comparison of the two study groups with respect to proximal contours and overhang formation; Chi-square test was applied and the level of significance was set at 0.05 There is a strong evidence base in favor of employing separation ring for class II composite restorations. The studies [4][5][6][11][12][13][14][15][16] in this regards actually recommend using separation ring in combination with sectional matrices. But it is not clear whether the positive results (tight contact) achieved by sectional matrix-separation ring assembly is attributed to the matrix or to the separation ring.…”
Section: Resultsmentioning
confidence: 99%
“…It has always remained a challenge for the dentists to obtain tight proximal contact with composites. 4 The clinical procedure of the proximal composite restoration has to compensate for the thickness of the matrix band as well as the polymerization shrinkage of the restorative material. 5 It was thought that employing thick consistency-packable composite could solve the problem but the 'packability' of the composite material has failed to achieve better contacts.…”
Section: Introductionmentioning
confidence: 99%